Development of spatial and temporal selectivity in the suprasylvian visual cortex of the cat - Zumbroich, T (J Neurosci, 1988)
We have studied the development of the spatial and temporal properties of neurons in the medial bank of the suprasylvian visual cortex (PMLS) in kittens aged between 9 d and 8 weeks. Quantitative measurements were made of the responses to drifting high-contrast gratings of optimum orientation and direction of motion, but varying in spatial and temporal frequency. The spatial resolution (“acuity”) of cells increased rapidly and was fully mature (over 2 cycles/deg for the best cells) at 3 weeks of age. The optimum spatial frequency also tended to improve and reached adult values (around 0.5 cycles/deg for the best cells) at about the end of the third week. In younger kittens, the spatial resolution of neurons was not obviously correlated with the eccentricity of their receptive fields, but in older animals acuity was clearly elevated for receptive fields in the central visual field. The proportion of “low-pass” cells (showing no obvious attenuation of response for gratings of low spatial frequency) decreased with age and simultaneously there was a slight increase in the mean spatial bandwidth of “bandpass” cells. Responses to drifting sinusoidal gratings were generally dominated by an unmodulated elevation of discharge at all ages. In tests with stationary, contrast-modulated gratings presented at different spatial positions, cells in the youngest kittens behaved nonlinearly and showed mainly an unmodulated increase in discharge, whereas in older kittens, as in adult cats, most neurons responded to contrast-modulated gratings with a small, phase- dependent response at the temporal frequency of modulation and a larger component at twice the fundamental frequency. None of the cells recorded at any age had a true “null position.” As in adult PMLS, the widths of receptive fields in kittens were, on average, about twice the size of the preferred spatial period (4 times the preferred bar width). At all ages, therefore, neurons in PMLS resembled striate complex cells with respect to the nonlinearity of their responses and the spatial structure of their receptive fields. The preferred temporal frequency and high-temporal-frequency cutoff also improved, on average, during the first 3 weeks of life, and the range of temporal frequencies over which cells responded continued to increase until at least 8 weeks. Although the low-spatial-frequency inhibition that creates spatial bandpass characteristics probably depends on cortical mechanisms, the postnatal development of both temporal and spatial resolution might well be limited by maturation at the level of the retina.